Analysis of Differentially Expressed Genes in Endothelial Cells Following Tumor Cell Adhesion, and the Role of PRKAA2 and miR-124-3p - Pan, Yan; Abdureyim, Marhaba; Yao, Qing; Li, Xuejun (Frontiers in Cell and Developmental Biology, 2021)
Tumor cell adhesion to endothelium is one pattern of tumor-endothelium interaction and one key step during tumor metastasis. The endothelium integrity is an important barrier to prevent tumor invasion and metastasis. Changes happened in ECs according to tumor cells adhesion provide important signaling mechanisms for the angiogenesis and metastasis of tumor cells. However, it is unclarified by now. In this present study we used Affymetrix Gene Chip Human Transcriptome Array 2.0. and quantitative real-time PCR (qPCR) to clarify the detailed genes alteration in endothelial cell adhered by prostate tumor cells PC-3M. A total of 504 differentially expressed mRNAs and 444 lncRNAs were obtained through chip data analysis. Gene Ontology (GO) function analysis showed that differentially expressed genes mainly mediated gland development and DNA replication at the biological level; at the cell component level, it was mainly involved in the mitochondrial inner membrane; at the molecular function level, it was mainly enriched in ATPase activity and catalytic activity. Kyoto Encyclopedia of Genes and Genomes (KEGG) signal pathway analysis showed that the differentially expressed genes mainly regulated pathways in cancer, cell cycle, pyrimidine metabolism and mTOR signaling pathway. Then we constructed protein-protein interaction functional network and mRNA-lncRNA interaction network using Cytoscape v3.7.2. to identify core genes, mRNAs and lncRNAs. And then, the miRNAs targeted by the core mRNA PRKAA2 were predicted using databases (miRDB, RNA22 and Targetscan). The qPCR result showed that miR-124-3p, predicted target miRNA of PRKAA2, was significantly down-regulated in endothelial cells adhered by PC-3M. Additionally, by using the knockdown lentiviral vectors of miR-124-3p to down-regulate miR-124-3p expression level in endothelial cells, we found the expression level of PRKAA2 was increased accordingly. Taken together, the adhesion of tumor cells had a significant effect on mRNAs and lncRNAs in the endothelial cells and in which PRKAA2 is a key molecule and miR-124-3p could regulate its expression and function in endothelial cells.